Nuclear Receptors in Regulation of Mouse ES Cell Pluripotency and Differentiation - Eimear M. Mullen; Peili Gu; Austin J. Cooney (PPAR Research)
Embryonic stem (ES) cells have great therapeutic potential because they are capable of indefinite self-renewal and have the potential to differentiate into over 200 different cell types that compose the human body. The switch from the pluripotent phenotype to a differentiated cell involves many complex signaling pathways including those involving LIF/Stat3 and the transcription factors Sox2, Nanog and Oct-4. Many nuclear receptors play an important role in the maintenance of pluripotence (ERRβ, SF-1, LRH-1, DAX-1) repression of the ES cell phenotype (RAR, RXR, GCNF) and also the differentiation of ES cells (PPARγ). Here we review the roles of the nuclear receptors involved in regulating these important processes in ES cells.